Detection of Aspergillus fumigatus PCR products by a microtitre plate based DNA hybridisation assay. - Fletcher, H; Barton, R; Verweij, P; Evans, E (1998)
AIMS: To develop a DNA based plate hybridisation assay for the detection of polymerase chain reaction (PCR) products amplified from Aspergillus fumigatus DNA; and to determine the sensitivity of this technique and compare it with Southern blotting. METHODS: A half-log dilution series of DNA extracted from A fumigatus was amplified with specific primers, one of which was 5' end labelled with biotin. PCR products were subsequently detected by agarose gel electrophoresis, Southern blotting, and binding of the products to a streptavidin coated microtitre well, followed by non-radioactive colorimetric detection. Amplification was carried out 10 times for each DNA dilution and a plot of initial DNA concentration against signal intensity was made. RESULTS: A DNA concentration of 1.5 pg could be detected by agarose gel electrophoresis and Southern blotting with a non-radioactively labelled aspergillus specific probe; 1.5 pg was detectable by streptavidin binding of the PCR products to a microtitre plate. The signal from the microtitre plate detection was proportional to the amount of DNA in the PCR reaction on a log-log scale between 100 and 1 pg of DNA. CONCLUSIONS: A DNA based plate hybridisation assay for the detection of A fumigatus PCR products is as sensitive as Southern blotting. However, results are obtained in three hours rather than the three days required for agarose gel electrophoresis, blotting, hybridisation, and detection.